(untitled) (Interdisciplinary Studies Journal, 2024)
This article presents practices related to the STEAM movement – ​​Science, Technology, Engineering, Art and Math – in the context of New High School in the state of Mato Grosso. Analyze possibilities and challenges of the STEAM movement for engaging young in full education and full-time education. Through bibliographical and documentary research, questionnaire application and data analysis via the policy cycle, it is noted that innovations are materializing in practice, aiming for greater involvement of young people, although it is necessary to consider the participation of the private, non-profit sector. Thus, the results found indicate that: most subjects consider that specific training took place in the state network on New High School; A significant number of managers declared that they knew the STEAM movement, while data from teachers showed that, of the 13 subjects, 06 said they were unaware of it. The majority identified that the school has already developed or is developing some STEAM action, activity or project and, regarding the format, the majority reported that this occurred in elective subjects, followed by an interdisciplinary project. The challenge of understanding the basis of High School reform in Mato Grosso is launched.